Ditinggalkan tapi Tidak Sendirian: Mazmur 27:10 dan Gambaran Kehilangan Orang Tua - Suryawinata, Samuel (Verbum Christi: Jurnal Teologi Reformed Injili, 2025)
Losing a parent is one of the most painful experiences in a person's life. Its impact can raise a profound existential question: "How do I live without them?" To answer this question, this article attempts to interpret Psalm 27:10 using a poetic-affective criticism approach that traces the psalmist's lamentation, emotions, recognition of God, and the dynamics of mood swings. By exploring the text of Psalm 27 in depth, it is found that the experience of being abandoned by parents does not lead the psalmist to loneliness but to a deeper recognition of God as light, salvation, and a fortress of life. This study also offers a new perspective on Psalm 27, namely as a reflection of mental and emotional health due to loss and loneliness, as well as a source of comfort and strength for those who are abandoned by their parents. In his solitude, the psalmist does not encounter emptiness but instead finds God, who welcomes him as a child.